Investigation of the composition of anabolic tablets using near infrared spectroscopy and Raman chemical imaging. Issue 3 (22nd July 2015) - Rebiere, Hervé; Ghyselinck, Céline; Lempereur, Laurent; Brenier, Charlotte
Abstract : The use of performance enhancing drugs is a widespread phenomenon in professional and leisure sports. A spectroscopic study was carried out on anabolic tablets labelled as 5 mg methandienone tablets provided by police departments. The analytical approach was based on a two‐step methodology: a fast analysis of tablets using near infrared (NIR) spectroscopy to assess sample homogeneity based on their global composition, followed by Raman chemical imaging of one sample per NIR profile to obtain information on sample formulation. NIR spectroscopy assisted by a principal components analysis (PCA) enabled fast discrimination of different profiles based on the excipient formulation. Raman hyperspectral imaging and multivariate curve resolution – alternating least square (MCR‐ALS) provided chemical images of the distribution of the active substance and excipients within tablets and facilitated identification of the active compounds. The combination of NIR spectroscopy and Raman chemical imaging highlighted dose‐to‐dose variations and succeeded in the discrimination of four different formulations out of eight similar samples of anabolic tablets. Some samples contained either methandienone or methyltestosterone whereas one sample did not contain an active substance. Other ingredients were sucrose, lactose, starch or talc. Both techniques were fast and non‐destructive and therefore can be carried out as exploratory methods prior to destructive screening methods. Copyright © 2015 John Wiley & Sons, Ltd. Abstract : A spectroscopic study of similar anabolic tablets was carried out in order to compare them and to determine their composition. The combination of NIR spectroscopy and Raman imaging assisted by chemometric enables the fast discrimination of samples, gives chemical images of the distribution of components, and succeeds in the identification of the excipients and the active substances. They are valuable tools for the analysis of samples of unknown composition.